2021
DOI: 10.1021/jacsau.1c00359
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Surface Reconstruction Unifies the Electrocatalytic Oxygen Evolution Performance of Nonstoichiometric Mixed Metal Oxides

Abstract: Compositionally versatile, nonstoichiometric, mixed ionic–electronic conducting metal oxides of the form A n +1 B n O 3 n +1 ( n = 1 → ∞; A = rare-earth-/alkaline-earth-metal cation; B = transition-metal (TM) cation) remain a highly attractive class of electrocatalysts for catalyzing the energy-intensive oxygen evolution reaction (OER). The current design strategies for desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 67 publications
1
32
1
Order By: Relevance
“…Electrocatalyst surface restructuring is induced by irreversible metal-site cation dissolution, resulting in in situ formation of a TM oxyhydroxide shell on top of the parent electrocatalyst core that serves as the active surface for OER. 210 For instance, Zhou et al 211 reported a simple self-sacrificing strategy to obtain high-performance OER electrocatalysts FeCo–oxyhydroxide. A trimetallic selenide heterostructure (FeCoMo–Se) consisting of FeSe 2 , CoSe 2 and MoSe 2 is first one-step synthesized on a carbon cloth substrate.…”
Section: Classification Of Transition Metal-based Oer Electrocatalyst...mentioning
confidence: 99%
“…Electrocatalyst surface restructuring is induced by irreversible metal-site cation dissolution, resulting in in situ formation of a TM oxyhydroxide shell on top of the parent electrocatalyst core that serves as the active surface for OER. 210 For instance, Zhou et al 211 reported a simple self-sacrificing strategy to obtain high-performance OER electrocatalysts FeCo–oxyhydroxide. A trimetallic selenide heterostructure (FeCoMo–Se) consisting of FeSe 2 , CoSe 2 and MoSe 2 is first one-step synthesized on a carbon cloth substrate.…”
Section: Classification Of Transition Metal-based Oer Electrocatalyst...mentioning
confidence: 99%
“…Here, leaching of cations , as well as structural modifications such as amorphization ,,,, and even complete decomposition of oxide catalysts , were observed and linked to changes in the catalysts’ activity. At the same time, recent studies have shown that near-surface phase transitions may play a key role in the catalytic process. ,, …”
Section: Introductionmentioning
confidence: 97%
“…At the same time, recent studies have shown that near-surface phase transitions may play a key role in the catalytic process. 8,12,28 Hence, it is apparent that surface phase transformations can trigger catalytic activity and are also involved in the aging of catalysts. The link between these processes however remains unresolved to date.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This effect would be difficult to achieve through direct synthesis of the active surface and provides a new way of using the modular nature of nonstochiometric MMOCs to generate catalytically active and stable active sites. 6 Professor Nikolla's contributions will be celebrated in an award symposium prepared in her honor at the ACS National Meeting this August in Chicago, Illinois. Please join us in congratulating her, hopefully also in person, at the award symposium this August!…”
mentioning
confidence: 99%
“…Prof. Nikolla has made significant contributions in the area of surface structure and nanostructure control in MMOCs as important electrocatalysts. She has developed approaches for correlating experimentally measurable oxide properties (i.e., oxide surface reducibility and electric conductivity) to their activity and stability for oxygen reduction and evolution reactions (critical chemical transformations for energy generation in fuel cells and carbon-neutral H 2 generation from water electrolysis, respectively). Her work revealed that the transition metal–lattice oxygen bond strength captures effects from both the oxide composition and crystal symmetry on the binding energetics of the oxygenated intermediates and consequently on the measured electrochemical activity and stability .…”
mentioning
confidence: 99%